Private Sector Consumption and Government Consumption and Debt in Advanced Economies : An Empirical Study - Mukherjee, Sanchita (IMF Working Papers; Working Paper ;, 2010)
This paper explores the hypothesis that the propensity to consume out of income varies in a non-linear fashion with fiscal variables, and in particular with government debt per capita. Using data from eighteen OECD countries the paper examines whether there is any empirical evidence to support the hypothesis that households move from non-Ricardian to Ricardian behavior as government debt reaches high levels and as uncertainty about future taxes increases. Our results provide support for this hypothesis, and also suggest that private and government consumption are substitutes in the household utility function.